Journey through the world of malaria - Yaro, Abubakar (Allergies and infectious diseases., 2014)
Our understanding of the pathogenic mechanisms of the malaria parasite has accumulated over the years with the advent of genomic knowledge playing a crucial role. Although great strides have been made in the field of malaria research, malaria still remains one of the most important public health issues in the world. Years ago, malaria was eradicated in some countries but global warming is playing a part in the spectacular re-emergence of malaria in some of these countries. There is still no effective vaccine, although some research has provided interesting data and anti-malaria drug resistance.